2019
DOI: 10.3390/jcm8010088
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Cross-Involvement in Autism Spectrum Disorders and Atopic Dermatitis: A Literature Review

Abstract: Autism Spectrum Disorder (ASD) is a category of neurodevelopmental disturbances seriously affecting social skills, to which the scientific community has paid great attention in last decades. To date, their pathogenesis is still unknown, but several studies highlighted the relevance of gene-environment interactions in the onset of ASD. In addition, an immune involvement was seen in a wide number of ASD subjects, leading several researchers to hypothesize a possible common pathogenesis between ASD and immune dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 118 publications
1
24
0
Order By: Relevance
“…The overlap of these miRNAs in ADHD and PedMS might be explained by common underlying mechanisms (e.g., their cognitive dysfunctions), since ADHD-like symptoms have been described in about 27% of PedMS cases [42]. According to the literature, miR-652-3p and miR-148b-3p were also found to be associated with autism [43]; this evidence may be justified by the clinical comorbidity between the two diseases that also seem to share some genetic background, thus complicating the differential diagnosis between them [44,45,46,47]. Furthermore, in our analysis, several DE miRNA targets were found to be associated with neuropsychiatric disorders, such as schizophrenia (TTN, SYNPO) [48,49], depressive disorder (PPARGC1B, TIMELESS) [50,51,52], and autism (TAF1, TRIO) [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The overlap of these miRNAs in ADHD and PedMS might be explained by common underlying mechanisms (e.g., their cognitive dysfunctions), since ADHD-like symptoms have been described in about 27% of PedMS cases [42]. According to the literature, miR-652-3p and miR-148b-3p were also found to be associated with autism [43]; this evidence may be justified by the clinical comorbidity between the two diseases that also seem to share some genetic background, thus complicating the differential diagnosis between them [44,45,46,47]. Furthermore, in our analysis, several DE miRNA targets were found to be associated with neuropsychiatric disorders, such as schizophrenia (TTN, SYNPO) [48,49], depressive disorder (PPARGC1B, TIMELESS) [50,51,52], and autism (TAF1, TRIO) [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of COL6A2 caused by the up-regulation of miR-29b is one of the underlying genetic mechanisms of ASD muscle disease and dyskinesia; miR-29b targets the ID3 gene. In addition, miR-29b is related to circadian rhythm signals, and studies have reported that ASD is associated with circadian rhythm disturbances [59] miR-103a-3p BDNF miR-103a-3p targets the brain-derived neurotrophic factor (BDNF) gene, BDNF is directly or indirectly involved in ASD, and BDNF plays a key role in neuronal differentiation and synapses [69] miR-146a ↑ GRIA3, MAP1B, KCNK2 miR-146a inhibits MAP1B, GRIA3, and KCNK2, therefore impairing ASD synaptic transmission and inhibiting neuronal migration; miR-146a contributes to neuroinflammation of ASD patients [53,70] miR-153 ↓ LEPR…”
Section: Mirnamentioning
confidence: 99%
“…Analyzing miRNA expression profiles in body fluids could reflect the real pathophysiologic processes of patients through very simple and non-invasive approaches, since brain tissue is not easily accessible (Kichukova et al, 2015). Despite many studies investigating whether miRNA might contain specific fingerprints for neurological and psychiatric disorders (Fineberg et al, 2009;Xu et al, 2012;De Sena Cortabitarte et al, 2018;Nguyen et al, 2018;Tonacci et al, 2019), only a few included Tourette syndrome (Rizzo et al, 2015;Cirnigliaro et al, 2017) and none is focused on AC and ACTS.…”
Section: Discussionmentioning
confidence: 99%